Pengenalan Teknologi Internet Berbasis Smartphone Untuk Wisata Kuliner Khas Melayu Bagi Ibu-Ibu Pengusaha Makanan Di Kecamatan Medan Labuhan - Khair, Ummul; S, Suriati; D, Dharmawati (Jurnal TUNAS, 2019)
The Community Engagement activity is done this time is to help the Malay traditional food entrepreneurs who can be said to be less commercial among other culinaries, because when the team Community Engagement conducts a survey to Medan Labuhan a few days ago, there were many Malay traditional food entrepreneurs complaining that their products were difficult to sell, not much demand. If you only expect local buyers, almost all people are good at cooking Malay food and cakes. This makes the team who is struggling in the field of IT to help these women to expand their business by utilizing the internet that uses smartphones to advertise the food they make. The number of culinary or foreign dishes that enter Indonesia does not require the possibility of preserving Indonesia's traditional culinary increasingly eroded by the times. Therefore preservation of traditional culinary must be done because it is part of Indonesian culture. Therefore, the use of technology is very important to preserve traditional culinary and convey it to the public, especially the young generation today.